Parametrization of all stable controllers stabilizing full state information systems and mixed sensitivity - Galindo Orozco, René (Professional Engineering Publishing, 2009)
Analytic expressions for the parametrization of all stable controllers of one and two-degrees-of-freedom stabilizing full sate information systems are presented. It is assumed that the strictly proper, lumped and linear time invariant nominal plant has a stabilizable realization and is strongly stabilizable, the number of the entries of the plant state is even and is the double of the number of the entries of the plant input. Right and left coprime factorizations of the transfer function of the plant in terms of the matrices of the plant realization are proposed, the Diophantine equation is solved and the stabilizing controllers are gotten using Youla parametrization. Conditions to get strong stability are given and the free parameters of the stabilizing controllers are fixed solving a mixed sensitivity problem. The results are illustrated through simulation examples of a half-car active suspension system and of a two degrees-of-freedom planar rotational robot.